2003
DOI: 10.1074/jbc.m209148200
|View full text |Cite
|
Sign up to set email alerts
|

Epidermal Growth Factor Receptor Mediates Increased Cell Proliferation, Migration, and Aggregation in Esophageal Keratinocytes in Vitro and in Vivo

Abstract: Epidermal growth factor receptor (EGFR) overexpression is observed in a number of malignancies, especially those of esophageal squamous cell origin. However, little is known about the biological functions of EGFR in primary esophageal squamous epithelial cells. Using newly established primary human esophageal squamous epithelial cells as a platform, we overexpressed EGFR through retroviral transduction and established novel threedimensional organotypic cultures. Additionally, EGFR was targeted in a cell type-a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
225
0
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 227 publications
(230 citation statements)
references
References 32 publications
4
225
0
1
Order By: Relevance
“…We showed that expressions of MMP-1, -3, -9 and -10 are inducible in T24 cells with EGF. The previous report showed that overexpression of EGFR in esophageal keratinocytes leads to the activation of STAT signaling pathway and enhanced expression of MMP-1 (Andl et al, 2003). By blocking STAT3 activity with the dominant-negative STAT3, we showed that STAT3 is required for an efficient induction of MMP-1 and MMP-10 by EGF.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…We showed that expressions of MMP-1, -3, -9 and -10 are inducible in T24 cells with EGF. The previous report showed that overexpression of EGFR in esophageal keratinocytes leads to the activation of STAT signaling pathway and enhanced expression of MMP-1 (Andl et al, 2003). By blocking STAT3 activity with the dominant-negative STAT3, we showed that STAT3 is required for an efficient induction of MMP-1 and MMP-10 by EGF.…”
Section: Discussionmentioning
confidence: 57%
“…Recent experimental evidence showed a link between EGFR-induced STAT activation and cell migration. Overexpression of EGFR in primary esophageal keratinocytes led to the activation of STAT signaling pathway, resulting in enhanced collagenase-1 expression and cell migration (Andl et al, 2003). STAT3 deficiency in epidermal keratinocytes stimulated cell adhesiveness to the substratum and inhibited EGF-and hepatocyte growth factor-inducible cell migration (Sano et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Although normal human esophageal keratinocyte culture has been reported from surgical specimens, 13,14 it is not easy to constantly obtain surgically acquired normal esophageal tissue. We recently established an esophageal-like stratified epithelial cell layer under ALI conditions using NHBE cells.…”
Section: Discussionmentioning
confidence: 99%
“…Shown are representative photomicrographs of two independent experiments; the target molecules are green and nuclei are red. 1999;Andl et al, 2003). Another report indicated that EGFR downregulation resulted in decreasing E-cadherin and catenins in ovarian carcinoma cells (Alper et al, 2000).…”
Section: Discussionmentioning
confidence: 99%